2014
DOI: 10.1038/ncomms4981
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the dynamics of clonal tumour evolution in vivo using secreted luciferases

Abstract: Tumours are heterogeneous cell populations that undergo clonal evolution during tumour progression, metastasis and response to therapy. Short hairpin RNAs (shRNAs) generate stable loss-of-function phenotypes and are versatile experimental tools to explore the contribution of individual genetic alterations to clonal evolution. In these experiments tumour cells carrying shRNAs are commonly tracked with fluorescent reporters. While this works well for cell culture studies and leukaemia mouse models, fluorescent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…Indeed, Lee et al. found a relation of early tumor recurrence and chromosomal instability with drug resistance . Misale et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Lee et al. found a relation of early tumor recurrence and chromosomal instability with drug resistance . Misale et al.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the heterogeneity and chromosome instability of cancer cells, targeted therapy may be compromised [24,25]. Indeed, Lee et al found a relation of early tumor recurrence and chromosomal instability with drug resistance [26][27][28]. Misale et al performed genotyping on cfDNA exacted from plasma of 24 patients with colorectal cancer, and showed that clinical resistance arose through the acquisition of mutations detected by cfDNA [22,29].…”
Section: Discussionmentioning
confidence: 99%
“…Lung colonization after i.v. tail vein injection of tumor cells was performed as previously described (39). In brief,…”
Section: Methodsmentioning
confidence: 99%
“…To quantitatively track the proliferation of knock-down cells in vivo, we coupled shRNA expression to secreted luciferases that accumulate in the blood of tumor-bearing mice and can be used as an artificial tumor marker for longitudinal monitoring of tumor burden (39). To directly compare knockdown and control cells within the same animal, we used a dual luciferase labeling approach (39). First, MDA-MB-231 cells were labeled with Gaussia luciferase (GLuc) in conjunction with shRNAs targeting mutp53, ENTPD5 or a nontargeting (nsh) control (Fig.…”
Section: Entpd5mentioning
confidence: 99%
“…After concentration, residue was purified by column chromatography (silica gel, hexane, ethyl acetate, then acetone) to yield 0.59 g (88%) of product 4 . 3 1 H NMR (400 MHz, CD 3 COCD 3 , ppm) δ 2.65 (t, J = 2.4 Hz, 1 H), 3.97 (d, J = 5.6 Hz, 2 H), 4.05 (dd, J = 5.6, 2.5 Hz, 2 H), 6.30 (s, 1 H), 7.17 (m, 1 H), 7.19 (s, 1 H), 7.79 (s, 1 H), 7.96 (d, J = 8.6 Hz, 1 H). Mass calculated for C 13 H 11 N 4 OS + (M + H + ) 271.065, found 271.064.…”
Section: Methodsmentioning
confidence: 99%